Frequency Dependent Electrical Properties of Hydrogen-Bonded Polymorph Diisopropylammonium Trichloroacetate (dipaTCA) - Ekramul Kabir (Journal of Scientific Research, 2025)
The hydrogen-bonded polymorph diisopropylammonium trichloroacetate (dipaTCA) exhibits intriguing electrical properties influenced by frequency-dependent behavior. dipaTCA are generally grown in the bulk by hydrothermal crystallization which produces several high-quality crystals. Frequency and temperature dependence of impedance and modulus spectroscopy, dielectric and ac conductivity are studied in the ranges of 1 kHz-20 MHz at 325-400K respectively. The measurements revealed significant frequency dispersion in both the real and imaginary components of the dielectric constant. The result of the Nyquist plot is found to be fitted with the theoretical Maxwell–Wegner capacitor model. The modulus data suggest that a hopping type mechanism of the system is present here. From the dielectric spectra the maximum value of permittivity (έ)max is nearly 20 at temperature 387K and frequency 10kHz. The activation energy (Ea) from the Arrhenius plot is also studied for the conduction mechanism of the material. These findings provide insights into the fundamental electrical properties of dipaTCA, positioning it as a candidate for applications in organic electronics and energy storage devices.